Effect of Variations of Cotton Fabric Dyeing on Chitosan-SiO2 Composite Solution on Hydrophobic Properties for Anti-Virus Mask - Yuliani, Kurnia Dwi; Ratnawulan, -; Fauzi, Ahmad; Gusnedi, -; Jonuarti, Riri (Department of Physics – Universitas Negeri Padang UNP, 2024)
The coronavirus Disease 2019 (Covid-19) has attracted worldwide attention since December 2019 and was declared a pandemic by the World Health Organization (WHO) on March 11. Covid-19 is believed to have originated in Wuhan, China, and has spread to more than 200 countries, every day the number of Covid-19 cases in the world continues to increase. One of the efforts to overcome Covid-19 is wearing a mask. This study aims to manufacture hydrophobic masks from cotton cloth that have antivirus properties from chitosan-SiO2 composite materials. This type of research is a laboratory experiment, Chitosan-SiO2 is used in the size of nanoparticles using a High Energy Milling (HEM) tool. Next, analyze the SiO2 content using X-Ray Fluorescence (XRF) and Infra Red Spectrophotometer (FTIR) to calculate the degree of deacetylation of chitosan. To analyze the crystal structure and crystal size using X-Ray Diffraction (XRD) and to determine the morphological structure of the Chitosan-SiO2 composite layer. The results of this study are hydrophobic masks derived from cotton cloth are anti-virus. The contact angles resulting from the variation of immersion are 122.4o, 130.914o, 134.563o, and 136.138o, while the contact angle without coating is 90o. The surface temperature produced from the Chitosan-SiO2 composite layer based on the temperature image pattern is 37.4oC, 39.9oC, 40.2o C, and 41.6oC. After washing the cotton fabric layer sample, contact angle melting occurs. The best variation of immersion against contact angles and antivirus tests characterized by surface temperature imagery patterns is 4 times dyeing with a contact angle of 136.138o reaching ultrahydrophobic angles and surface temperatures of 41.6oC.